Design of broadband multilayer dichroic coating for a high-efficiency solar energy harvesting system - Jiachen, Wang; Lee, Sang Bae; Lee, Kwanil (OPTICAL SOC AMER, 2015)
We report on the design and performance of a broadband dichroic coating for a solar energy conversion system. As a spectral beam splitter, the coating facilitates a hybrid system that combines a photovoltaic cell with a thermal collector. When positioned at a 45 degrees angle with respect to incident light, the coating provides high reflectance in the 40-1100 nm and high transmission in the 1200-2000 nm ranges for a photovoltaic cell and a thermal collector, respectively. Numerical simulations show that our design leads to a sharp transition between the reflection and transmission bands, low ripples in both bands, and slight polarization dependence. (C) 2015 Optical Society of America
Keywords: REFRACTIVE-INDEX; OPTICAL COATINGS; REFINEMENT; THICKNESS; FILMS